2018
DOI: 10.1590/2317-1782/20182017064
|View full text |Cite|
|
Sign up to set email alerts
|

Atenção Básica como ordenadora do cuidado ao bebê de risco para alterações do neurodesenvolvimento

Abstract: Purpose Characterize infants at risk of neurodevelopmental disorders according to sociodemographic and health profiles and describe their monitoring in Basic Health Units (UBS) under different management models. Methods Data were collected from medical records of infants at risk of neurodevelopmental disorders in the west region of the city of Sao Paulo from August 2013 to February 2014 (phase 1 - characterization; phase 2 - monitoring). Results Of the 225 individuals assessed in the first phase of the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
0
5
0
6
Order By: Relevance
“…This question is important for monitoring risk infants, since there is an increased chance of perinatal and childhood diseases in this population. The at-risk newborn must be accompanied in PHC until the second year of life, aiming to health promotion, protection and early detection of changes that may affect the child’s quality of life 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This question is important for monitoring risk infants, since there is an increased chance of perinatal and childhood diseases in this population. The at-risk newborn must be accompanied in PHC until the second year of life, aiming to health promotion, protection and early detection of changes that may affect the child’s quality of life 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis for the high score detected is the monitoring of child’s growth in PHC, usually addressed in a consistent way 27 , since it is linked to commonly emphasized biological factors 23 . As for development, previous study found that over 56% of records gathered in FHS and tBHU showed no information relating to development milestones 27 , suggesting that monitoring might not be effective. This potential weakness may be masked by the simultaneous approach of these two aspects in the same question 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O estudo de Molini-Avejonas et al 10 demonstra que existem lacunas no monitoramento do desenvolvimento de bebês na Atenção Primária, visto que, identificar e avaliar fatores de risco para o desenvolvimento do bebê e orientar sobre a relação do ambiente como forma de estimular o desenvolvimento, são maneiras eficazes de prevenir e intervir precocemente em possíveis atrasos do desenvolvimento infantil.…”
Section: Artigo Originalunclassified